2006
DOI: 10.1086/505958
|View full text |Cite
|
Sign up to set email alerts
|

A Flight to Domesticity? Making a Home in the Gentlemen's Clubs of London, 1880–1914

Abstract: use the terms "upper class" and "elite" throughout the article to refer to the membership of gentlemen's clubs. Clubmen were aristocrats, politicians, and men at the top of the business, professional, and military worlds. This would include men from both the landed aristocracy and the upper middle class or the aristocracy of talent. A more detailed exploration of membership can be found in my dissertation, "Clubland: Masculinity, Status, and Community in the Gentlemen's Clubs of London, c. 1880-1914" (PhD diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…He shows that the writings of the Irish rifleman Patrick MacGill sustained a heroic interpretation of the war and his own role in it. The masculine world of the late Victorian and Edwardian gentleman's club is examined by Milne‐Smith, who argues that, far from embodying a flight from domesticity, as is often suggested, clubs served many of the functions of a home, for both single and married men. In a prize‐winning essay, Hamlett investigates the decoration of student rooms at Royal Holloway and Oxbridge colleges in the late nineteenth century, finding many similarities between men's and women's rooms, and in particular a willingness among men to adopt ‘feminine’ decoration.…”
Section: (V) 1850–1945
Mark Freeman and Julian Greaves
University Of mentioning
confidence: 99%
“…He shows that the writings of the Irish rifleman Patrick MacGill sustained a heroic interpretation of the war and his own role in it. The masculine world of the late Victorian and Edwardian gentleman's club is examined by Milne‐Smith, who argues that, far from embodying a flight from domesticity, as is often suggested, clubs served many of the functions of a home, for both single and married men. In a prize‐winning essay, Hamlett investigates the decoration of student rooms at Royal Holloway and Oxbridge colleges in the late nineteenth century, finding many similarities between men's and women's rooms, and in particular a willingness among men to adopt ‘feminine’ decoration.…”
Section: (V) 1850–1945
Mark Freeman and Julian Greaves
University Of mentioning
confidence: 99%
“…This emerges in Quintin Colville's study of shipboard material culture in the British navy, in this collection, and Amy Milne-Smith's examination of male domesticity in the club. 13 Smith's analysis is, however, confined to the upper classes. Deborah Cohen's recent study has confirmed that nineteenth-century middle-class men were often active purchasers of goods for the home.…”
mentioning
confidence: 99%